CORRELATION OF STEM STUDENTS’ PERFORMANCE IN THE NATIONAL CAREER ASSESSMENT EXAMINATION AND ACADEMIC SUBJECTS - Ferrer, Flordeliza P.; Cruz, Roberto J. (PEOPLE: International Journal of Social Sciences, 2017)
The study aims to determine if the students’ performance in the National Career Assessment Examination (NCAE) is significantly correlated to their academic performance in the succeeding grade levels. NCAE is a career direction program through an aptitude test administered to students. The academic subjects considered in the study include Science, Mathematics and English; while the grade levels take account of Grade 9 (through NCAE results), and Grades 10 and 11. The researchers employed the purposive sampling, taking into consideration the selection of students who qualified in the required cut-off score/grade for admission in the academic track of Science, Technology, Engineering and Mathematics (STEM). The statistical findings revealed that the learners got the highest grade in Science both in NCAE and Grade 10, while English in Grade 11. Significant positive correlations of the students’ performance were consistently observed in the three academic areas and in the three grade levels. This pattern is indicative of: (1) a proper career assessment conducted that guide the learners in choosing the academic track where they have better aptitude or potential; (2) a sensible screening criteria set in selecting students to be admitted in the STEM track; and (3) an evidence of quantified judgments on the learners’ academic achievements per grade level as a product of the design of the spiral curriculum.